Adverse reactions to ophthalmic medicines. (December 2017) - Badyal, K.K.; Badyal, I.S.
Abstract : Summary: Drugs used topically in the eye can cause systemic adverse effects that can range from mild to fatal. Ocular drugs can cause adverse effects by draining through the nasolacrimal duct and being absorbed into the blood stream, or by precipitating in the eye, or by causing an increase in intraocular pressure.